EFFECTIVENESS OF THE IMPLEMENTATION OF ELECTRONIC-BASED GOVERNMENT SYSTEMS IN ORDER TO IMPROVE PUBLIC SERVICES (Survey of Sungai Penuh City Government) - Kurniadi, Hendi (Archives of Business Research, 2019)
This study aims to determine the policies of the Sungai Penuh city government in the implementation of electronic, governance and service-based government systems and to find out whether electronic-based government systems can improve public services in Sungai Penuh City. The data in this study are primary data obtained from questionnaires distributed directly to respondents and the results of interviews with research informants. Analysis of research data was carried out qualitatively and quantitatively using descriptive analysis. The results of this study prove that the Sungai Penuh City government policy in implementing the Electronic-Based Government System is contained in Sungai Penuh city Mayor Regulation No. 12 of 2013. The Governance of Electronic-Based Governance System is managed temporarily by the Sungai Penuh City Communication, Information and Statistics Service. Electronic-based government system services available include electronic-based government administration services and electronic-based public services. The implementation of an electronic-based government system in improving public services in Sungai Penuh City has not been effective Keywords: Effectiveness, E-Government, Public Services